2021
DOI: 10.1016/j.heliyon.2021.e07101
|View full text |Cite
|
Sign up to set email alerts
|

How do political coups disrupt Fiji's tourism? Impact assessment on ecotourism at Koroyanitu National Heritage Park (KNHP), Abaca

Abstract: The nexus between mass tourism and politics has been widely validated in tourism literature; nonetheless, the impacts of political putsches on ecotourism are understudied in the context of the Pacific Islands, i.e., Fiji. This study aims to investigate how Fiji's political upheavals impacted ecotourism after examining ecotourist arrivals and revenue generated at KNHP from its inception till 2018. Additionally, it presents a comparative analysis of Fiji coups on tourism and ecotourism and examines the recovery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Similarly, in politically unstable destinations, a negative correlation has been found between attitude and DI (Eid et al, 2019). Similarly, Kundra et al (2021) argue that political instability has a negative effect on DI. Literature has shown that in stable contexts, a favourable DI is more likely to lead to a favourable attitude towards visiting the destination (Huang and Van der Veen, 2019 in China;Song et al, 2014 in South Korea).…”
Section: Perceived Destination Imagementioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, in politically unstable destinations, a negative correlation has been found between attitude and DI (Eid et al, 2019). Similarly, Kundra et al (2021) argue that political instability has a negative effect on DI. Literature has shown that in stable contexts, a favourable DI is more likely to lead to a favourable attitude towards visiting the destination (Huang and Van der Veen, 2019 in China;Song et al, 2014 in South Korea).…”
Section: Perceived Destination Imagementioning
confidence: 92%
“…The impact of media coverage on the DI and PR associated with visiting such destinations is critical (Garg, 2015). For example, the widespread circulation of images depicting violence and political unrest in Fiji by international media in 2000 resulted in a significant blow to Fijian tourism as many countries issued travel advisories advising their citizens to avoid Fiji (Kundra et al , 2021). It is, therefore, essential to understand that even though a crisis may be temporary, significant attention given by conventional and social media may enhance tourist concerns for a long period (Jin et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Fiji is described as the ‘lands of smiles’. Desai (1973) and Harrison and Pratt (2010) state that Fiji's tourism became the highest foreign exchange earner between the 1960s and 2010, but the political instability induced by the coups of 1987, 2000 and 2006 has resulted in a drop in tourism ( Kundra et al., 2021 ). According to Hall (1996) , geographic isolation, limited terrestrial resources and infrastructure, limited landmass and mineral resources and weak industrial growth are all issues that Fiji faces.…”
Section: Study Areamentioning
confidence: 99%
“…Moreover, political stability in a destination is a critical factor influencing tourists' safety. Political instability is also acknowledged as a factor that undermines tourists' sense of safety (Bianchi and Milano, 2024; Kundra et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%